Preparation of hybrid particles via surface-initiated polymerization from thiol-functionalized attapulgite and their application in polycarbonate as an efficient processing modifier. Issue 10 (3rd October 2021) - Yang, Haicun; Cai, Zinan; Li, Runfei; Ma, Wenzhong; cao, Zheng; Gong, Fanghong; Tao, Guoliang; Liu, Chunlin
ABSTRACT: In this work, the thiolized attapulgite (ATP-MTS) particles were prepared by the dealcoholation between hydroxyl and γ-mercaptopropyltrimethoxysilane (MTS). Then, based on the 'grafting from' mechanism, the surface-initiated graft polymerization was carried out to give ATP grafted with polymethyl methacrylate hybrid particles (ATP@PMMA). The grafting process was characterized in detail by FTIR, TGA, XRD, XPS, TEM and elemental analysis. The effects of the main polymerization conditions on the grafting ratio were investigated in detail. Finally, polycarbonate (PC) was modified with ATP@PMMA to investigate the effects of hybrid particles on the processability of nanocomposites. The results showed that ATP@PMMA particles with a maximum graft ratio of 23.3% were prepared successfully within 5 h. The optimum polymerization temperature was 60°C, and the ratio of MMA/SH/AIBN was 500/2/1. The surface tailoring improved the dispersion of ATP@PMMA in the matrix. Compared with the pristine PC, the incorporation of ATP@PMMA enhanced the melt flow index (MFI), while reduced the glass transition temperature ( T g ) and complex viscosity of nanocomposites. Graphical Abstract: uf0001